Surgical and Patient-Reported Outcomes of Autologous versus Implant-Based Reconstruction following Infected Breast Device Explantation. Issue 6 (29th March 2022) - Asaad, Malke; Slovacek, Cedar; Mitchell, David; Liu, Jun; Selber, Jesse C.; Clemens, Mark W.; Chu, Carrie K.; Mericli, Alexander F.; Butler, Charles E.
Abstract : Background: Implant-based breast reconstruction infections often require implant explantation. Whereas some plastic surgeons pursue autologous reconstruction following the first implant-based breast reconstruction failure caused by infection, others argue that a second attempt is acceptable. Methods: The authors conducted a retrospective study of patients who underwent a second reconstruction attempt with implant-based or free flap breast reconstruction following explantation because of infection between 2006 and 2019. Surgical and patient-reported outcomes were compared between the two groups. Results: A total of 6093 implant-based breast reconstructions were performed during the study period, of which 130 breasts met our inclusion criteria [implant-based, n = 86 (66 percent); free flap, n = 44 (34 percent)]. No significant differences in rates of overall (25 percent versus 36 percent; p = 0.2) or major (20 percent versus 21 percent; p = 0.95) complications were identified between the free flap and implant-based cohorts, respectively. Implant-based breast reconstruction patients were more likely to experience a second infection (27 percent versus 2 percent; p = 0.0007) and reconstruction failure (21 percent versus 5 percent; p = 0.019). Among irradiated patients, reconstruction failure was reported in 44 percent of the implant-based and 7 percent of the free flap cohorts ( p = 0.02). Free flap patients reported significantly higher scores for Satisfaction with Breasts (73.7 ± 20.1 versus 48.5 ± 27.9; p = 0.0046). Conclusions: Following implant-based breast reconstruction explantation because of infection, implant-based and free flap breast reconstruction had similar rates of overall and major complications; however, implant-based breast reconstruction had considerably higher rates of infection and reconstructive failures and lower patient-reported scores for Satisfaction with Breasts. Given the high rates of implant-based breast reconstruction failure in patients with prior radiotherapy and infection-based failure, plastic surgeons should strongly consider autologous reconstruction in this patient population. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.